2010
DOI: 10.1007/s11998-010-9308-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of fluorine-containing poly-styrene-acrylate latex with core–shell structure using a reactive surfactant

Abstract: Fluorine-containing poly-styrene-acrylate (PSA) latex with core-shell structure was successfully synthesized by seeded semicontinuous emulsion polymerization using fluorine monomer Actyflon-G 04 and reactive emulsifier DNS-86. The chemical composition, morphology of latex, and surface composition of the latex film were characterized by Fourier transform infrared spectra, transmission electron microscopy, and X-ray photoelectron spectroscopy, respectively. The stability properties of latex were tested by Ca 2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Based on the XPS spectrum, the intensity of the signal coming from fluorine (F1s) was higher in the film-air interface than in film-glass interface. Migration of fluorinecontaining groups from the copolymer structure to the filmair interface results from a decrease in the free energy in the surface of the latex film [45]. Examples of XPS spectra demonstrating the surface composition and deconvoluted C1s profile are presented in the Fig.…”
Section: Methods Of Particle Surface Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the XPS spectrum, the intensity of the signal coming from fluorine (F1s) was higher in the film-air interface than in film-glass interface. Migration of fluorinecontaining groups from the copolymer structure to the filmair interface results from a decrease in the free energy in the surface of the latex film [45]. Examples of XPS spectra demonstrating the surface composition and deconvoluted C1s profile are presented in the Fig.…”
Section: Methods Of Particle Surface Analysismentioning
confidence: 99%
“…The morphology of particles composed of a polystyrene core with a shell of polyacrylate containing fluorine was successfully determined by depositing of a diluted particle suspension on a carbon-coated copper grid, staining it with 1.0 wt% phosphotungstic acid (PTA) for 3 min and drying it [45]. The use of phosphotungstic acid also allowed for successful determination of the structure of particles composed of a poly(methyl methacrylate) core and a hydrophilic shell made of biopolymers or polymers containing amine groups, such as casein, gelatin, chitosan, branched poly(ethylene imine), poly(allylamine) [66] or poly(vinylamine) [67].…”
Section: Protein Adsorption Investigationsmentioning
confidence: 99%
“…The polymerizable emulsifier could be chemically bonded to the PUs to avoid long‐term leaching, and it is therefore more environmentally friendly than conventional emulsifiers. In addition, since the PU emulsion was dispersed in water via self‐emulsification, the preparation of fluorinated polyurethane–acrylate (FPUA) emulsions could be considered as a soap‐free emulsion polymerization . Transmission electron microscopy (TEM) was used to observe the morphology of PU and FPUA emulsions, and the results showed that fluorine could aggregate onto the surface of FPUA particles during the formation of the core–shell structure.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the development of soap-free emulsion polymerization [8,9] and reactive surfactants [10][11][12] has promoted the substantial improvement of the resistance to water of the polyacrylate latex films. In order to improve the adhesion properties of polyacrylate emulsions, the tackifying resins especially rosin resin and its derivatives have attracted more and more attentions.…”
Section: Introductionmentioning
confidence: 99%